Exploring Subjective Income Inequality in Europe and MENA Regions - Szczepaniak, Małgorzata; Osińska, Magdalena; Koubaa, Salah (Bulletin of Geography. Socio-economic Series, 2025)
This article examines the relationship between income inequalities and attitudes toward them in Europe, the Middle East, and North Africa (MENA) regions, representing the world’s most equal and unequal regions. Utilizing data from the joint European Values Survey - World Values Survey, World Income Inequality Database, and the Standardized World Income Inequality Database, the study uncovers significant differences in subjective inequalities between these regions and assesses the impact of internal income stratifications within societies. The key findings demonstrated significant differences in subjective inequalities between the European and MENA regions, which are not confirmed within the regions. Generally, there is a greater acceptance of income inequalities in MENA countries than in Europe. The results also revealed that in Europe, attitudes toward income inequalities are more diversified within income class stratification, with higher income classes tending to have a more positive attitude towards income inequalities than lower ones.